An Examination of the Putative Role of Melatonin in Exosome Biogenesis - Amini, Hassan; Rezabakhsh, Aysa; Heidarzadeh, Morteza; Hassanpour, Mehdi; Hashemzadeh, Shahriar; Ghaderi, Shahrouz; Sokullu, Emel; Rahbarghazi, Reza; Reiter, Russel J. (Frontiers in Cell and Developmental Biology, 2021)
During the last two decades, melatonin has been found to have pleiotropic effects via different mechanisms on its target cells. There is an abundance of data for some aspects of the signaling pathways within cells while other casual mechanisms have not been adequately addressed. From an evolutionary perspective, eukaryotic cells are equipped with a set of interrelated endomembrane systems consisting of intracellular organelles and secretory vesicles. Of these, exosomes are touted as cargo-laden secretory vesicles that originate from the endosomal multivesicular machinery which participate in a mutual cross-talk at different cellular interfaces. It has been documented that cells transfer various biomolecules and genetic elements through exosomes to sites remote from the original cell in a paracrine manner. Findings related to the molecular mechanisms between melatonin and exosomal biogenesis and cargo sorting are the subject of the current review. The clarification of the interplay between melatonin and exosome biogenesis and cargo sorting at the molecular level iwill help to define a cell's secretion capacity. This review precisely addresses the role and potential significance of melatonin in determining the the efflux capacity of cells via the exosomal pathway. Certain cells, for example, stem cells actively increase exosome efflux in response to melatonin treatment which accelerates tissue regeneration after transplantation into the injured sites.